The Lake El'gygytgyn scientific drilling project - conquering Arctic challenges through continental drilling - Martin Melles (Institut für Geologie und Mineralogie); Julie Brigham-Grette (Department of Geosciences); Pavel Minyuk (North-East Interdisciplinary Science Research Institute FEB RAS); Christian Köberl (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Andrei Andreev (Universität Köln); Timothy Cook (University of Massachusetts, Amherst); Grigory Fedorov (Arctic and Antarctic Research Institute); Catalina Gebhardt (Alfred Wegener Institut für Polar- und Meeresforschung (AWI)); Eeva Haltia-Hovi (Helmholtz-Center Potsdam German GeoResearchCenter); Maaret Kukkonen (Universität Köln); Norbert Nowaczyk (Helmholtz-Center Potsdam German GeoResearchCenter); Georg Schwamborn (Alfred Wegener Institut für Polar- und Meeresforschung (AWI)); et al. (Scientific Drilling, 2011)
The abstract is available here: https://uscholar.univie.ac.at/o:243642 The abstract is available here: https://uscholar.univie.ac.at/o:243642